Professional forecasters' expectations, consistency, and international spillovers - Joscha Beckmann; Robert L. Czudaj (Journal of Forecasting, 2020)
This paper focuses on the expectation formation process of professional forecasters by relying on survey data on forecasts regarding gross domestic product growth, consumer price index inflation and 3-month interest rates for a broad set of countries. We examine the interrelation between macroeconomic forecasts and also the impact of uncertainty on forecasts by allowing for cross-country interdependencies and time variation in the coefficients. We find that professional forecasts are often in line with the Taylor rule and identify significant expectation spillovers from monetary policy in the USA.
Keywords: 519; expectations; forecasts; survey data; uncertainty